The Influence Of Organizational Justice And Organizational Culture On Psychological Contracts With Work-Life Balance As A Mediating Variable - Lindawati Lindawati (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to determine the effect of organizational justice and organizational culture on the psychological contract, with work-life balance as a mediating variable among employees of CV Media Gravika Yogyakarta. Using a quantitative method with a survey approach, the research involved 45 permanent employees selected through a census technique. Data were analyzed using Partial Least Square – Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between variables. The results show that organizational culture has a positive and significant effect on the psychological contract, indicating that a supportive and value-driven work environment strengthens employees' perceptions of mutual obligations with the organization. Organizational justice is also found to significantly influence work-life balance, suggesting that fair treatment and transparent policies contribute to employees' ability to manage work and personal life demands. However, work-life balance does not mediate the relationship between either organizational justice or organizational culture and the psychological contract, indicating that the psychological contract is shaped more strongly by direct organizational practices than by employees' perceptions of work-life harmony. These findings highlight the importance of fostering fairness and cultivating a constructive organizational culture to enhance employee commitment, trust, and psychological attachment, ultimately supporting a more harmonious, motivated, and productive organizational climate.